Periodontal Disease on Pregnant Women (Case Study: Pondok Labu Village, South Jakarta, Indonesia) - Rikawarastuti Rikawarastuti; Ngatemi Ngatemi; Nita Noviani Harahap (International Journal of Public Health Science (IJPHS), 2016)
During preganancy, women periodically concern about ANC due to fetus growth, but ignore their own periodontal health. This research was conducted to acknowledge the effect of age, educational background, parity, body mass index (BMI), diabetes mellitus, smoking habit and oral hygiene with periodontal disease on pregnant women. Analytical observation study with cross sectional design was conducted to pregnant women in Pondok Labu Village (Kelurahan), South Jakarta. Purposive sampling was performed among 101 respondents. Chi Square and logistic regression were used for the analysis.  Results shown that periodontal disease on pregnant women were 73.2% (66.3% were calculus and 6.9% were having periodontal pocket of 4-5 mm). It is proven that there is relationship between age, educational background, parity, BMI, diabetes mellitus, and smoking habit to the periodontal disease. On the other hand, oral hygiene highly affected the periodontal disease on pregnant woman. Poor oral hygiene is the dominant factor of periodontal disease on pregnant women after being controlled by age (OR= 21.33, p value 0.005). It is advised for pregnant women to improve their knowledge on how to care for their oral hygiene prior to and during pregnancy, as well as, go through treatments with dentists.